ANALISIS RASIO LIKUIDITAS, SOLVABILITAS DAN RENTABILITAS PADA COMMANDITAIRE VENNOOTSCHAP (CV) SUMBER REZEKI DI TANAH GROGOT - Ika Nurhazanah; Amir Hamzah; Erni Susanti (Paser Institute Of Accounting and Finance, 2023)
The researcher formulated the research problem, namely "What is the level of Liquidity, Solvency and Profitability ratios in Commanditaire Vennootschap (CV) Sumber Rezeki based on financial reports for the period 2020, 2021 and 2022" with the research objective namely "To analyze the level of Liquidity, Solvency and Profitability ratios on CV. "Source of Fortune based on financial reports for the periods 2020, 2021 and 2022." The results of the research that the researchers got were as follows: Analysis of the liquidity ratio shows that the company in fulfilling its short-term obligations is in a fairly good condition. With a current ratio in 2020 of 8.57 times, in 2021 of 7.41 times and in 2022 of 0.1 times. The quick ratio in 2020 was 8.57 times, in 2021 it was 7.41 times, and in 2022 it was 0.1. The cash ratio in 2020 was 822%, in 2021 it was 718%, and in 2020 it was 4%. The solvency ratio analysis shows that the company is in good condition in fulfilling all of its obligations. The Debt to Asset Ratio in 2020 is 12%, in 2021 it is 13%, and in 2022 it is 70%. Debit to Equity in 2020 is 13%, in 2021 is 15%, and in 2022 is 24%, the Long Term Debt to Equity Ratio in 2020, 2021 and 2022 cannot be analyzed due to the unavailability of long term liabilities. The profitability ratio analysis shows that the profit margin calculation results for 2020 are 11%, 2021 are 23%, and in 2022 are 11%. Net Profit Margin in 2020 will be 8%, in 2021 it will be 10%, and in 2022 it will be 6%. Return on Investment in 2020 will be 15%, in 2021 it will be 29% and in 2022 it will be 31%. Return on Equity in 2020 was 17%, in 2021 it was 34%, and in 2022 it was 104